Pengaruh Penempatan Kerja, terhadap Kinerja Pegawai dengan Kompetensi Sebagai Variabel Intervening : Studi pada Dinas Pemuda Olahraga dan Pariwisata Daerah Kabupaten Morowali - Muh Agus; Mohammad Ega Nugraha (Jurnal Ekonomi Manajemen Akuntansi, 2026)
This Study aims to examine the effect of job placement on employee performance through competence as an intervening variable the sample consisted of 64 employees of the Regional Office of Youth, Sport, and Tourism of Morowali Regency. The sampling technique used was saturated sampling. Data were collected using questionnaires and anlyzed with the assistance of the SmartPLS 4 program. The result of the study indicate that job placement and competence have a direct thourism of Morowali Regency. In addition, job placement has an indirect effect on employee performancethtougt competence at the same institution. The coefficient of determination shows an R-square value of 0,182, indicating that 18.2% of the experience, while 80.8% is influenced by other factors not examined in this study. Meanwhile, competence obtained an R-square value of 1.134, indicating that 13.4% of the variance in competence is influenced by job placement, while 80.6% is influenced by other variable not examined is this study.